Reduced Expression of Immune Mediators by T-Cell Subpopulations of Combat-Exposed Veterans With Post-Traumatic Stress Disorder - Xiong, Ying; Wang, Zhewu; Young, M. Rita I. (Frontiers in Psychiatry, 2019)
Post-traumatic stress disorder (PTSD) has been suggested to be associated with an inflammatory immune state, although few studies have examined peripheral blood lymphocytes in subjects that have PTSD and compared immune parameters to subjects that experienced similar trauma, but did not develop PTSD. An exploratory approach was undertaken to compare phenotypes of blood CD4+ and CD8+ subpopulations and their expression of immune mediators between Veterans of the Iraq and Afghanistan wars who experienced similar levels of combat, with some developing PTSD and other not. The results of this study did not demonstrate evidence of enhanced immune activation of peripheral blood lymphocytes. Instead, the results showed a decline in expression of the pro-inflammatory mediator IFN-g and the cytotoxin granzyme B in CD8+ subpopulations from Veterans with PTSD. While the reductions in expression of IFN-g and granzyme B did not reach statistical significance when examining the CD8+ cell population as a whole, the declines were significant when examining the CD8+ cell subpopulations, with different mediators being reduced in different subpopulations. The most prominent decline in IFN-g expression was by the unconventional CD8dimCD3+ T-cell subpopulation that has been associated with chronic infection and immune fatigue. The decline in granzyme B was most prominent in the NK-containing CD8dimCD3- subpopulation of T cells. Consequently, analysis of blood leukocyte subpopulations, rather than bulk lymphocyte groups, reveals a dampened level of immune reactivity in combat-exposed Veterans with PTSD compared to combat-exposed Veterans without PTSD.